2018
DOI: 10.1097/md.0000000000013107
|View full text |Cite|
|
Sign up to set email alerts
|

Primary hyperparathyroidism characterized by diffuse homogeneous metastatic pulmonary calcification

Abstract: Rationale:Primary hyperparathyroidism (PHPTI) with respiratory tract symptom is extremely rare. It is caused by autonomic oversecretion of parathyroid hormone (PTH) owing to parathyroid adenoma, hyperplasia, or tumor. The diagnosis of PHPTI often needs to be made based on medical history, clinical manifestation, laboratory tests, and imaging examination. Moreover, no study has reported PHPTI with diffuse metastatic pulmonary calcification (MPC) as the characteristic.Patient concerns:A 49-year-old female from Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“… 9 To our knowledge, there have been few reports of patients with a parathyroid adenoma who presented with symptoms suggesting metastatic microcalcification in lungs and stomach. 4 7 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 9 To our knowledge, there have been few reports of patients with a parathyroid adenoma who presented with symptoms suggesting metastatic microcalcification in lungs and stomach. 4 7 …”
Section: Discussionmentioning
confidence: 99%
“… 10 – 15 Data from the few reports of metastatic microcalcification due to parathyroid adenoma have shown that the deposition tends to occur in the stomach, kidneys, heart and lungs, with the pulmonary system being particularly susceptible. 4 7 , 16 The pathogenic mechanisms of metastatic microcalcification have yet to be elucidated but most reports suggest that hypercalcaemia and a local alkaline environment may contribute to the condition. 17 In the case presented here, the patient had hypercalcaemia due to PHPT and impaired kidney function, which would have resulted in a decrease in the excretion of excess calcium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the article, “Primary hyperparathyroidism characterized by diffuse homogeneous metastatic pulmonary calcification: A case report”, [1] which appears in Volume 97, Issue 44 of Medicine , the authors would like to note a change in author order. The author order should be Yuzhu Jia, Lihua Wang, Guangzhao Yang, Guoqun Mao, Yougen Cheng, Yulin Cao.…”
mentioning
confidence: 99%